Determinants of Food Security in Kenya, a Gender Perspective - Kassie, Menale; Ndiritu SW; Shiferaw, Bekele (2012)
The paper contributes to an understanding of the determinants of food security with a bias on the link between gender of household head and food security using detailed farm household and plot level survey data from 30 divisions in rural Kenya. Both parametric and non-parametric econometric techniques are used to ensure robustness of the results from the econometric analyses. Since the assumption of pooled regression is rejected, we run separate food security regressions at plot level both for Male Headed Households (MHHs) and Female Headed Households (FHHs). Both descriptive and econometrics results shows that FHHs in general are more likely to be food insecure compared to their male counterparts. The analysis further reveals that Female Headed Households food security increases with quality of extension workers; land quality, farm size while distance to the market reduces the probability of food security. For the quality of extension staff, policy makers should focus on improving the skill of extension staff for efficient and effective dissemination of technologies and other important information that has impact on food security. Since area expansion is infeasible due to land scarcity in Kenya, policy makers focusing on land augmenting practices can help farm households to escape food insecurity.